ANALISIS REGULASI UJI KLINIS ALAT KESEHATAN DI INDONESIA: TINJAUAN TERHADAP PERATURAN MENTERI KESEHATAN NOMOR 63 TAHUN 2017 - Gunawan Widjaja; Wagiman; Dyah Ersita Yustanti; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (Jurnal Kesehatan, 2025)
The development of medical device technology in Indonesia has prompted the need for strict supervision to ensure the safety, quality, and usefulness of products before they are distributed. Minister of Health Regulation No. 63 of 2017 serves as the legal basis for conducting clinical trials of medical devices, which aims to standardise the testing process and ensure the protection of test subjects. This study analyses the provisions and implementation of the regulation, identifying challenges related to human resources, facilities, bureaucracy, and inter-sectoral coordination that remain major obstacles in the field. Using a normative method and a descriptive qualitative approach, the study examines the substance of the regulation, its implementation mechanisms, and its effectiveness in supporting innovation and protecting the public. The findings indicate that the effectiveness of Permenkes 63/2017 is highly dependent on enhancing the capacity of implementing personnel, harmonising regulations with international standards, and strengthening oversight and inter-institutional coordination. Strategic recommendations are proposed for regulatory reform, human resource capacity building, and optimising the management of clinical trial data to make Indonesia's medical device oversight system more credible and adaptive to technological advancements.